Identification of the Position of Subsurface Aquifers and the Distribution of Groundwater Level Depth in Oksibil District, Pegunungan Bintang Regency - Semuel Rorrong; Wika Matana Nion; Erwin Erwin; M. Suliswanto; Riswandy Loly Paseru (Jurnal Indonesia Sosial Teknologi, 2024)
Groundwater is dynamic and influenced by natural factors, such as geology and geomorphology, which affect aquifer characteristics, groundwater movement, and surface morphology. This study aims to identify subsurface aquifer positions and the distribution of groundwater depth in Oksibil District, Pegunungan Bintang Regency. The research utilizes the resistivity geoelectric method with a Wenner configuration to determine lithology and aquifer characteristics. Measurements were conducted using the AIDU Golden Rod instrument, which analyzes natural electric fields. Results indicate the presence of pressurized aquifers at depths ranging from 125 to 300 meters with varying thicknesses of 20 to 85 meters. In contrast, free aquifers are primarily located at shallow depths (0–40 meters) in specific areas, such as Kabiding. The findings provide valuable insights into groundwater resource management and regional aquifer potential in Pegunungan Bintang Regency